Strategies for Developing Toasted Bread SMEs in the Face of Modern Culinary Competition - Wildan Khoirul Sani; Ardhan Syacharie Wardana; Rahma Ayu Jaskia (Young Journal of Social Sciences and Humanities, 2025)
This study explores the development strategies employed by toast-based micro, small, and medium enterprises (MSMEs) to remain competitive in the increasingly dynamic and competitive modern culinary market. The research focuses on several key aspects, including product innovation, enhancement of raw material quality, improvement of customer service, utilization of digital technology, and strengthening of local branding. Data were collected through literature review, market observation, and a qualitative descriptive approach, allowing an in-depth understanding of business practices and challenges faced by these enterprises. The findings indicate that toast-based MSMEs enhance their competitiveness through several strategies. Product innovation, such as flavor differentiation and creative menu offerings, allows businesses to cater to diverse consumer preferences. Improvements in product hygiene and ingredient quality further increase consumer trust and satisfaction. Additionally, digital marketing through social media platforms enables broader market reach and more effective engagement with customers. Collaboration with culinary communities and local influencers also strengthens brand visibility and customer loyalty. These strategies collectively contribute to expanded market share and sustainable growth despite the fast-changing food trends. The study provides practical insights and can serve as a reference for MSMEs seeking to implement adaptive, creative, and long-term development strategies in the modern culinary industry.